Defect-engineered magnetic responsive ldh-based bone repair material and preparation method and application thereof

CN122768488APending Publication Date: 2026-09-18TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611220853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0005]为了解决现有现有骨修复材料成骨诱导能力不足、难以高效促进间充质干细胞成骨分化的技术问题,本发明目的在于提供一种缺陷工程调控的磁响应型LDH基骨修复材料及其制备方法和应用,通过调控材料组成与结构,利用缺陷工程调控和磁响应策略的协同作用显著增强骨材料的骨修复效果

Benefits of technology

1、本发明通过缺陷工程调控的LDH基材料与磁性四氧化三铁纳米颗粒复合而成得到LDH基骨修复材料,缺陷工程调控的LDH基材料由传统层状双氢氧化物经碱刻蚀处理得到的中空结构的独立六边形孔的晶体材料,显著增加了材料的比表面积和活性位点,提升了材料的生物学活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122768488A_ABST
    Figure CN122768488A_ABST
Patent Text Reader

Abstract

This invention discloses a defect-engineered, magnetically responsive LDH-based bone repair material, its preparation method, and its applications, relating to the field of biomedical nanomaterials. The LDH-based bone repair material of this invention is composed of a defect-engineered LDH-based material and magnetic iron oxide nanoparticles. The defect-engineered LDH-based material is a hollow, independently hexagonal porous crystalline material obtained by alkaline etching of traditional layered double hydroxides. This invention also provides applications of the defect-engineered, magnetically responsive LDH-based bone repair material in the preparation of drugs that promote osteogenic differentiation of mesenchymal stem cells and in drugs for bone defect repair and regeneration. Due to its unique magneto-biological effect, the defect-engineered, magnetically responsive LDH-based bone repair material can efficiently promote osteogenic differentiation of mesenchymal stem cells and promote bone tissue repair and regeneration, showing broad application prospects in the field of bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical nanomaterials, and in particular to a defect-engineered magnetically responsive LDH-based bone repair material, its preparation method, and its application. Background Technology

[0002] Every year, tens of millions of people in my country suffer from various tissue and organ defects. How to effectively repair and reconstruct the function of damaged tissues and organs is a major scientific and technological challenge that urgently needs to be addressed in the field of clinical medicine. Among these challenges, the repair and regeneration of bone defects has always been a key focus and difficulty in clinical treatment. Existing bone repair materials struggle to simultaneously achieve good biocompatibility, suitable mechanical properties, controllable degradation characteristics, and efficient osteogenic induction capabilities, thus limiting their clinical application effectiveness.

[0003] Mesenchymal stem cells (MSCs) possess excellent proliferative capacity, self-renewal properties, and multi-lineage differentiation potential, making them ideal seed cells for bone defect repair and regeneration, providing a stable source of cells for bone tissue repair. However, in current technological systems, the autonomous osteogenic differentiation capacity and osteogenic efficiency of MSCs are limited, making it difficult to meet the high-efficiency repair needs of large-area, critical bone defects, thus hindering the clinical translation and application of stem cell bone regeneration technology.

[0004] Layered double hydroxides (LDHs) are a class of two-dimensional nanomaterials with a layered structure. Due to their unique anion exchange capacity, good biocompatibility, and pH-responsive degradation characteristics, they show great promise in drug delivery and bone tissue engineering. However, traditional LDH materials suffer from limited specific surface area and insufficient active sites, which restricts their further development of biological activity. Defect engineering strategies, by introducing controllable defect structures (such as vacancies and pores) into the material, can effectively increase active sites and improve ion transport performance, thereby significantly enhancing the material's biological effects. Furthermore, the introduction of magnetic response strategies can achieve controlled localization and deep tissue penetration of the material, synergistically promoting bone tissue regeneration. Summary of the Invention

[0005] To address the technical problems of insufficient osteogenic induction capacity and difficulty in efficiently promoting osteogenic differentiation of mesenchymal stem cells in existing bone repair materials, this invention aims to provide a defect-engineered, magnetically responsive LDH-based bone repair material, its preparation method, and its application. By regulating the material composition and structure, the synergistic effect of defect engineering regulation and magnetic response strategies significantly enhances the bone repair effect of the bone material.

[0006] The first aspect of this invention provides a defect-engineered magnetically responsive LDH-based bone repair material, wherein the defect-engineered magnetically responsive LDH-based bone repair material is composed of a defect-engineered LDH-based material and magnetic iron oxide nanoparticles, denoted as Mag-HLF; the defect-engineered LDH-based material is a hollow-structured crystalline material with independent hexagonal pores obtained by alkaline etching of traditional layered double hydroxides, and the overall structure of the material presents a hexagonal unit morphology with a hollow structure.

[0007] Furthermore, the general formula of the conventional nanolayered double hydroxide is [M 2+ (1-x) M 3+ x [OH)2]x + [A n- ] x / n·zH2O, where M 2+ It is a divalent metal cation, M 3+ A is a trivalent metal cation. n- M is an anion with an interlayer valence of n, X is the molar ratio of trivalent cations to all cations, z is the number of water molecules of crystallization between each nanolayered double hydroxide molecule, and M is the anion with an interlayer valence of n. 2+ and M 3+ The salts formed are all soluble.

[0008] Furthermore, the M 2+ Mg 2+ The M 3+ For Al 3+ The A n- CO3 2- ; Mg in the material 2+ With Al 3+ The molar ratio is (1-x):x = 3:1-5:1.

[0009] The second aspect of this invention provides a method for preparing the above-mentioned defect-engineered magnetically responsive LDH-based bone repair material, comprising the following steps: S1. Preparation of traditional layered double hydroxides: Dissolve soluble divalent metal ion salts and soluble trivalent metal ion salts in water to prepare metal ion salt solutions. Use double-distilled water (without CO2) as a solvent to prepare urea solutions. Mix the metal ion salt solutions and urea solutions, transfer them to a hydrothermal synthesis reactor, heat at 100°C for 24 h, and dry to obtain traditional layered double hydroxides. S2. Preparation of defect-engineered LDH-based materials: Using double-distilled water with CO2 as a solvent, an alkaline solution was prepared. The traditional layered double hydroxide obtained in S1 was dispersed in the prepared alkaline solution, transferred to a hydrothermal synthesis reactor, heated at 160℃ for 5 h, and dried to obtain the defect-engineered LDH-based material. S3. Composite magnetic iron oxide nanoparticles: The defect-engineered LDH-based material obtained in step S2 is composited with magnetic iron oxide nanoparticles to obtain a defect-engineered magnetically responsive LDH-based bone repair material.

[0010] Furthermore, the concentration of the urea solution in step S1 is 0.04 M.

[0011] Further, the soluble divalent metal ion salt in step S1 is selected from either magnesium nitrate or magnesium chloride; the soluble trivalent metal ion salt is selected from either aluminum nitrate or aluminum chloride. Furthermore, the molar ratio of divalent metal ions to trivalent metal ions in step S1 is 3:1 to 5:1.

[0012] Furthermore, the molar amount of urea: (M 2+ and M 3+ Total molar quantity) = 3-5 : 1.

[0013] Further, the alkaline solution mentioned in step S2 is a potassium hydroxide solution or sodium hydroxide solution with a concentration of 0.5-2 M.

[0014] Furthermore, in step S2, the ratio of the traditional layered double hydroxide to the alkaline solution is 1.5-2 mg / mL, and the concentration of the alkaline solution is 0.5-2 mol / L.

[0015] Furthermore, in step S3, the mass ratio of the defect-engineered LDH-based material to the magnetic iron oxide nanoparticles ranges from 1:0.2 to 1:0.8.

[0016] Furthermore, in step S3, the composite magnetic iron oxide nanoparticles are adsorbed using an electrostatic adsorption method, the specific steps of which are as follows: (1) Disperse the prepared defect-engineered LDH-based material in double-distilled water to remove carbon dioxide and prepare an LDH-based dispersion; (2) Carboxylated iron oxide magnetic nanoparticles were dispersed in carbon dioxide-free double-distilled water to prepare a magnetic particle dispersion; (3) The carboxylated iron oxide magnetic nanoparticle dispersion was added dropwise to the LDH-based dispersion under continuous stirring. The mixture was fully mixed and reacted by electrostatic adsorption to obtain the LDH-based magnetic composite suspension. (4) The LDH-based magnetic composite suspension is washed and dried to obtain the defect-engineered magnetically responsive LDH-based bone repair material.

[0017] Furthermore, the composite magnetic iron oxide nanoparticles in step S3 are synthesized using an in-situ co-precipitation method, the specific steps of which are as follows: (1) Dissolve soluble ferrous salts and soluble ferric salts in double-distilled water to remove carbon dioxide and prepare ferric ion precursor solutions; (2) Prepare an alkaline precipitant solution using ethylene glycol or diethylene glycol as a solvent; (3) The defect-engineered LDH-based material, iron ion precursor solution and alkaline precipitant solution prepared in step S2 are mixed and stirred until homogeneous. The mixture is then heated to 160-220 °C and reacted at a constant temperature for 4-6 h to obtain an LDH-based magnetic composite suspension. (4) The LDH-based magnetic composite suspension was washed and dried to obtain a magnetically responsive LDH-based bone repair material with defect engineering control.

[0018] Further, the soluble divalent ferric salt in step (1) is selected from any one of ferrous sulfate, ferrous chloride, and ferrous nitrate; the soluble trivalent ferric salt is selected from any one of ferric sulfate, ferric chloride, and ferric nitrate. Furthermore, the molar ratio of divalent iron ions to trivalent iron ions in step (1) is 1:1 to 1:2.

[0019] The third aspect of this invention provides the application of the above-mentioned defect-engineered magnetically responsive LDH-based bone repair material in the preparation of drugs that promote osteogenic differentiation of mesenchymal stem cells and in drugs for the repair and regeneration of bone defects.

[0020] Furthermore, the mesenchymal stem cells are bone marrow-derived mesenchymal stem cells or osteoblastic progenitor cells.

[0021] Furthermore, the animal model used when applying the application in vivo is a critical bone defect model of the skull in 8-10 week old male C57BL / 6 mice.

[0022] Compared with the prior art, the present invention has achieved the following beneficial technical effects: 1. This invention obtains an LDH-based bone repair material by combining a defect-engineered LDH-based material with magnetic iron oxide nanoparticles. The defect-engineered LDH-based material is a hollow, independently hexagonal pore crystal material obtained by alkaline etching of traditional layered double hydroxides, which significantly increases the specific surface area and active sites of the material, thereby enhancing its biological activity.

[0023] 2. The Mag-HLF material prepared in this invention has good biocompatibility. The cell survival rate test results show that after treatment of rBMSCs with different concentrations of Mag-HLF material for 48 h, the cell survival rate is higher than 85%, indicating that the material has good biocompatibility and magnetic modification does not significantly increase cytotoxicity.

[0024] 3. The Mag-HLF material prepared in this invention can efficiently promote osteogenic differentiation of mesenchymal stem cells. The results of alkaline phosphatase (ALP) staining and alizarin red staining showed that the number of calcium nodules increased and the staining was deeper in the ARS staining of each Mag-HLF group, indicating that Mag-HLF can significantly promote osteogenic differentiation of rBMSC cells, and the promoting effect is positively correlated with the Fe3O4 loading.

[0025] 4. The Mag-HLF material prepared by this invention has excellent effects in in vivo bone defect repair. Through in vivo bone defect repair evaluation experiments, it is shown that Mag-HLF can significantly promote bone defect repair under the action of an external static magnetic field. The magnetic response effect, together with the porous framework structure of the material, can significantly enhance cell adhesion ability and strengthen the osteogenic differentiation behavior of stem cells, effectively improving the bone regeneration and repair effect in the bone defect area.

[0026] In summary, this invention provides a defect-engineered, magnetically responsive LDH-based material to promote osteogenic differentiation of mesenchymal stem cells. Cell viability testing, osteogenic differentiation alkaline phosphatase staining, and Alizarin Red mineralization staining results showed that the Mag-HLF material treatment group exhibited significantly increased alkaline phosphatase activity and mineralized nodule formation levels, with deeper staining. In vivo experiments on critical bone defect repair in C57BL / 6 mice confirmed that Mag-HLF material with static magnetic field intervention achieved the largest new bone coverage area. This defect-engineered, magnetically responsive LDH-based composite material can efficiently promote osteogenic differentiation of mesenchymal stem cells and has broad application prospects in the field of bone defect repair. Attached Figure Description

[0027] Figure 1 (A) is a scanning electron microscope image of the nanomaterial Mag-HLF 2 in Example 1 of the present invention; Figure 1 (B) is a transmission electron microscope image of the nanomaterial Mag-HLF2 in Example 1 of the present invention; Figure 1 (C) is the X-ray diffraction (XRD) characterization diagram of the nanomaterial Mag-HLF 2 in Example 1 of the present invention.

[0028] Figure 2 The results are the hysteresis curves (VSM) characterization results of the vibrating sample magnetometers of HLF nanomaterials and various groups of Mag-HLF in the embodiments of the present invention.

[0029] Figure 3The results (CCK8) show the cytotoxicity of BMSCs treated with different concentrations of Mag-HLF nanomaterials 48 h after treatment. The horizontal axis represents the concentration of each material, and the vertical axis represents the cell viability of BMSCs. The viability of the blank control group was set to 100%.

[0030] Figure 4 The results of alkaline phosphatase staining and alizarin red staining of HLF materials and Mag-HLF materials of various groups in this invention after 7 days of differentiation of BMSC / MC3T3 under external magnetic field treatment are shown.

[0031] Figure 5 The results are MicroCT characterization results of the control group and the nanomaterials HLF and Mag-HLF in Example 1 of this invention after applying and not applying a magnetic field to a mouse skull defect model. The corresponding bar charts are the quantitative analysis results of bone mineral density (BMD) and bone volume fraction (BV / TV). Detailed Implementation

[0032] To make the technical means, creative features, objectives and effects of this invention easier to understand, the following describes in detail the preparation method of a nanocomposite material that promotes osteogenic differentiation of mesenchymal stem cells, in conjunction with embodiments and accompanying drawings.

[0033] Mesenchymal stem cells (MSCs) are a type of stem cell that can differentiate into adult cells such as bone, cartilage, and fat in different culture systems. They have advantages such as short experimental cycles, sensitive indicators, and ease of standardization in experimental research. In this invention, rat bone marrow-derived mesenchymal stem cells (BMSCs) are mainly used for experiments.

[0034] In the following examples, the BMSCs used were purchased from Guangzhou Cyagen Biosciences Co., Ltd.; the high-glucose DMEM, fetal bovine serum, and penicillin / streptomycin (double antibiotics) used were essential components of the cell culture medium for maintaining normal cell growth and were commercially available products purchased from Gibco, USA; the dexamethasone, sodium ascorbate, β-glycerophosphate, and 1,25-dihydroxyvitamin D3 used in the culture medium for osteogenic differentiation of BMSCs were purchased from Merck Sigma-Aldrich, Germany. Other non-self-made reagents and raw materials were generally commercially available products.

[0035] In the following examples, a preparation method based on the metal ion composition change of nanolayered double hydroxide (LDH) was adopted, and BMSCs treated with various magnetically responsive LDH-based materials were subjected to osteogenic differentiation. The experimental results showed that various magnetically responsive LDH-based materials all had different degrees of effect on promoting osteogenic differentiation of BMSCs. The material synthesis method with the best effect is shown in Example 1, and other types of materials are shown in Examples 2-6.

[0036] Example 1: Preparation of Defect-Enhanced Magnetically Responsive LDH-Based Bone Repair Material The specific steps for preparing defect-engineered LDH-based material HLF and defect-engineered magnetically responsive LDH-based material Mag-HLF2 are as follows: (1) Prepare a 40 mL solution of a metal ion salt using 10 mmol magnesium nitrate and 2 mmol aluminum nitrate, wherein Mg 2+ With Al 3+ The molar ratio between them is 5:1.

[0037] (2) Using CO2-free ddH2O (double-distilled water) as a solvent, prepare 20 mL of 0.04 M urea solution. Mix 40 mL of the metal ion salt solution obtained in step (1) with 20 mL of the urea solution obtained in step (2), transfer to a hydrothermal synthesis reactor, and heat at 100 °C for 24 h to obtain the first suspension.

[0038] (3) The first suspension was dried in a vacuum drying oven to obtain the traditional nano-layered double hydroxide LDH.

[0039] (4) Prepare 60 mL of alkaline solution using 60 mmol of potassium hydroxide.

[0040] (5) Take 0.1 g of the LDH obtained in step (3) and disperse it in 60 mL of the solution prepared in step (4). Transfer it to a hydrothermal synthesis vessel and heat it at 160 °C for 5 h to obtain the second suspension.

[0041] (6) After drying the second suspension in a vacuum drying oven, the defect-engineered LDH-based material is obtained, denoted as HLF. The HLF used in the HLF group is the HLF material prepared in this step.

[0042] (7) Disperse 1 mg HLF in 1 mL of double-distilled water (excluding carbon dioxide) to prepare an HLF dispersion; (8) Disperse 0.4 mg of carboxylated iron oxide in 1 mL of double-distilled water to remove carbon dioxide and prepare iron oxide dispersion; (9) The iron oxide dispersion was added dropwise to the HLF dispersion under continuous stirring. The mixture was fully mixed and reacted by electrostatic adsorption to obtain the Mag-HLF 2 suspension.

[0043] The microstructure of the Mag-HLF composite material was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM); the phase composition of Mag-HLF was qualitatively analyzed using X-ray diffraction (XRD); and the magnetic properties of the material were quantitatively characterized using a vibrating sample magnetometer (VSM).

[0044] Figure 1 (AC) shows the scanning electron microscope (SEM), transmission electron microscope (TEM), and XRD results of Mag-HLF, a magnetically responsive LDH-based material with defect engineering control, in embodiments of the present invention. The results are as follows: Figure 1 A and Figure 1 As shown in Figure B, Mag-HLF retains the hexagonal framework structure of HLF, with a large number of nanoparticles with a diameter of approximately 12-16 nm uniformly loaded on the framework surface. Figure 1 As shown in Figure C, Mag-HLF exhibits characteristic diffraction peaks of layered double hydroxides at 2θ = 11.5°, 23.1°, 34.8°, 46.5°, and 60.2°, consistent with the standard card in PDF#44-1482; simultaneously, characteristic diffraction peaks of Fe3O4 appear at 2θ = 30.1°, 35.5°, 43.1°, 57.0°, and 62.6°, consistent with the standard card in PDF#25-1402. These results indicate that Fe3O4 was successfully loaded onto the HLF framework without disrupting the layered structure of HLF.

[0045] Example 2 The difference from Example 1 is that the Mg in the metal ion salt solution prepared in step (1) is different. 2+ With Al 3+ The molar ratio between the metal ions was 3:1. The remaining operations were the same as in Example 1. Mag-HLF material was successfully obtained. XRD characterization showed that the obtained material had a layered structure similar to that of Example 1 and characteristic Fe3O4 diffraction peaks, indicating that the target material could still be successfully prepared at a metal ion ratio of 3:1.

[0046] Example 3 The difference from Example 1 is that the Mg in the metal ion salt solution prepared in step (1) is different. 2+ With Al 3+ The molar ratio between them was 1:1. The remaining operations were the same as in Example 1. Ultimately, a hollow framework HLF material was not successfully obtained. This result indicates that Mg... 2+ With Al 3+ The molar ratio needs to be maintained at 3:1 or higher to form a stable hexagonal hollow frame structure.

[0047] Example 4 The difference from Example 1 is that in step (9), the mass ratio of the defect-engineered LDH-based material to the magnetic iron oxide nanoparticles in the HLF suspension and iron oxide suspension is 1:0.2. The remaining operations are the same as in Example 1. Mag-HLF 1 material was successfully obtained.

[0048] Example 5 The difference from Example 1 is that in step (9), the mass ratio of the defect-engineered LDH-based material to the magnetic iron oxide nanoparticles in the HLF suspension and iron oxide suspension is 1:0.8. The remaining operations are the same as in Example 1. Mag-HLF 3 material was successfully obtained.

[0049] Example 6 The difference from Example 1 is that the iron(III) oxide suspension prepared in step (8) is directly synthesized by in-situ deposition based on step (7). Specifically, the HLF dispersion is mixed with Fe... 2+ / Fe 3+ After mixing the solutions (molar ratio 1:2), NH3·H2O was added as a precipitant, and the mixture was stirred at 80°C for 2 h to allow Fe3O4 nanoparticles to grow in situ on the surface of the HLF framework. The remaining operations were the same as in Example 1. Mag-HLF4 material was successfully obtained.

[0050] Figure 2 The magnetic properties of the nanomaterial Mag-HLF in this embodiment of the invention were characterized using a vibrating sample magnetometer (VSM) to test the hysteresis loops of HLF (non-magnetic) and Mag-HLF 1 / 2 / 3 in a magnetic field range of -20 kOe to 20 kOe. The results show that HLF exhibits no significant magnetic response, with saturation magnetization close to zero; while Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 all exhibit typical superparamagnetic properties, with saturation magnetizations of approximately 12, 22, and 35 emu / g, respectively, increasing with increasing Fe3O4 loading. Both remanent magnetization and coercivity are close to zero, indicating that the materials have no remanence after the external magnetic field is removed, which is beneficial for in vivo applications.

[0051] The control group (Ctrl) undergoes no additional material processing and is set as a blank control.

[0052] I. The procedure for cell viability testing (CCK-8) is as follows: Step 1: Culture rat bone marrow-derived mesenchymal stem cells (BMSCs).

[0053] BMSCs were seeded into 96-well plates at a density of 8000 cells / well and cultured in medium at 37°C and 5% CO2 for 18–24 h for subsequent material processing. The BMSC medium consisted of MEM and 10% fetal bovine serum. In this experiment, the culture time was 24 h.

[0054] Step two: Prepare three suspensions, each with five concentrations: Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 suspensions, with concentrations of 5 μg / mL, 10 μg / mL, 20 μg / mL, 40 μg / mL, and 80 μg / mL, respectively.

[0055] Step 3: Discard the supernatant from the cultured BMSCs in Step 1. Add different concentrations of Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 suspensions prepared in Step 2 to each well. After culturing for 48 h, add 10 μL of CCK-8 solution to each well. After incubating in the dark for 4 h, measure the OD (optical density) value at 450 nm using a microplate reader. The results are shown below. Figure 3 .

[0056] Figure 3 This data represents the cytotoxicity results (CCK-8 assay) of BMSCs treated with different concentrations of Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 nanomaterials in Examples 1, 4, and 5 of this invention after 48 h. The horizontal axis represents the concentration of each material, and the vertical axis represents the cell viability of BMSCs. The viability of the blank control group was set to 100%.

[0057] like Figure 3 As shown, within the concentration range of 0-80 μg / mL, the cell viability of the three Mag-HLF materials for rBMSCs was higher than 85%, indicating that the materials have good biocompatibility and that magnetic modification did not significantly increase cytotoxicity.

[0058] II. Alkaline phosphatase and Alizarin Red staining during osteogenic differentiation 1. Alkaline phosphatase (ALP) staining BMSCs were seeded onto 12-well plates at a density of 1×10⁶. 5Cells were cultured in medium at 37°C and 5% CO2 for 18-24 h until a cell confluence density of 70% was reached, at which point they were used for subsequent material processing. The composition of the BMSC osteogenic differentiation medium was: MEM; 10% fetal bovine serum; 0.1 μmol / L dexamethasone; 20 μg / mL sodium ascorbate; 10 mM β-glycerophosphate. HLF and Mag-HLF solutions were prepared using BMSC osteogenic differentiation medium to achieve a material concentration of 5 µg / mL in each group. After 7 days of differentiation, the cells were fixed with 4% paraformaldehyde, and the osteogenic differentiation effect was detected by alkaline phosphatase (ALP) activity.

[0059] Figure 4 (A, C) show ALP staining of BMSCs and MC3T3 cells treated with Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 nanomaterials in Examples 1, 4, and 5 of this invention for 7 days, in the control group and in the control group. Compared with the HLF group, the ALP staining of all Mag-HLF groups was significantly darker, and the effects of Mag-HLF 2 and Mag-HLF 3 groups were better than those of Mag-HLF 1 group. This indicates that Mag-HLF can significantly promote osteogenic differentiation of rBMSCs and MC3T3 cells.

[0060] 2. Alizarin Red staining BMSCs were seeded onto 12-well plates at a density of 1×10⁶. 5 Cells were cultured in medium at 37°C and 5% CO2 for 18-24 h until a cell confluence density of 70% was reached, at which point they were used for subsequent material processing. The composition of the BMSC osteogenic differentiation medium was: MEM; 10% fetal bovine serum; 0.1 μmol / L dexamethasone; 20 μg / mL sodium ascorbate; and 10 mM β-glycerophosphate. Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 suspensions were prepared using BMSC osteogenic differentiation medium to achieve a material concentration of 5 µg / mL in each group. After 14 days of differentiation, the cells were fixed with 4% paraformaldehyde and stained with Alizarin Red to detect the osteogenic differentiation effect.

[0061] Figure 4 (B) Alizarin Red staining of BMSCs treated with Mag-HLF 1, Mag-HLF 2, and Mag-HLF 3 nanomaterials in Examples 1, 4, and 5 of this invention for 14 days. The results showed that the Mag-HLF groups exhibited increased numbers of calcium nodules and deeper staining in ARS staining, with the Mag-HLF 2 group showing better results than the Mag-HLF 1 and Mag-HLF 3 groups. This indicates that Mag-HLF can significantly promote osteogenic differentiation of rBMSCs, and the promoting effect is positively correlated with the Fe3O4 loading.

[0062] III. Evaluation of Mag-HLF in vivo bone defect repair Eight-week-old C57BL / 6 mice were selected to construct a 3 mm diameter cranial bone defect model and randomly divided into five groups: Ctrl group (blank control, no material implanted), HLF group, Mag-HLF group (Magne-HLF2 implanted), Ctrl-ON group (blank control + magnetic field), and Mag-HLF-ON group (Magne-HLF2 implanted + magnetic field). The materials for each group were implanted into the bone defect. The Mag-HLF-ON and Ctrl-ON groups received external static magnetic field stimulation (1 hour daily, 7 days weekly) postoperatively. Animals were sacrificed at 6 and 12 weeks postoperatively, and cranial specimens were collected for Micro-CT scanning. Three-dimensional reconstruction was performed to observe the bone defect repair, and bone mineral density (BMD) and bone volume fraction (BV / TV) were quantitatively analyzed.

[0063] Figure 5 The results are Micro-CT scans and quantitative analysis of bone mineral density (BMD) and bone volume fraction (BV / TV) of skull specimens from mice treated with skull defects for 6 and 12 weeks, respectively, in the control group and the Mag-HLF2 group of Example 1 of this invention.

[0064] Depend on Figure 5 It was observed that at 6 weeks post-surgery, significant new bone formation was observed at the bone defect site in the Mag-HLF-ON group, while the repair effects in the other groups were relatively poor. At 12 weeks post-surgery, the Mag-HLF-ON group exhibited the largest bone defect repair area, with new bone density approaching that of the surrounding normal bone tissue. Quantitative analysis showed that the BMD and BV / TV values ​​in the Mag-HLF-ON group were significantly higher than those in the other groups (P<0.01), with the BV / TV value reaching approximately 42%, approaching the level of normal bone tissue. This indicates that Mag-HLF2 can significantly promote bone defect repair under the influence of an external static magnetic field. The magnetic response effect, combined with the porous framework structure of the material, can significantly enhance cell adhesion and strengthen stem cell osteogenic differentiation behavior, effectively improving the bone regeneration and repair effect in the bone defect area.

[0065] IV. The role and effect of Mag-HLF in Example 1 The Mag-HLF prepared in this embodiment of the invention, combined with cell viability detection, alkaline phosphatase staining, alizarin red mineralization staining, and in vivo evaluation of critical cranial bone defect repair, shows that this material can significantly promote osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), increase alkaline phosphatase expression levels and the amount of mineralized nodules formed; after intervention with a static magnetic field, it can significantly expand the new bone coverage area at the bone defect site and accelerate bone tissue regeneration in the defect area. In summary, the Mag-HLF prepared in this embodiment of the invention possesses excellent osteogenic differentiation-promoting properties and has broad application prospects in the field of bone defect repair.

[0066] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention.

Claims

1. A defect-engineered, magnetically responsive LDH-based bone repair material, characterized in that, The material is composed of a defect-engineered LDH-based material and magnetic iron oxide nanoparticles. The defect-engineered LDH-based material is a hollow, independently hexagonal pore crystal material obtained by alkaline etching of traditional layered double hydroxides. The overall structure of the material presents a hexagonal unit morphology with a hollow structure.

2. The defect-engineered, magnetically responsive LDH-based bone repair material according to claim 1, characterized in that, The general formula of the traditional nanolayered double hydroxide is [M 2+ (1-x) M 3+ X [OH)2]x + [A n- ] x / n ·zH2O, where M 2+ It is a divalent metal cation, M 3+ A is a trivalent metal cation. n- M is an anion with an interlayer valence of n, X is the molar ratio of trivalent cations to all cations, z is the number of water molecules of crystallization between each nanolayered double hydroxide molecule, and M is the anion with an interlayer valence of n. 2+ and M 3+ The salts formed are all soluble; the M 2+ Mg 2+ The M 3+ For Al 3+ The A n- CO3 2- ; Mg in the material 2+ With Al 3+ The molar ratio is (1-x):x = 3:1-5:

1.

3. A method for preparing a defect-engineered, magnetically responsive LDH-based bone repair material according to any one of claims 1-2, characterized in that, Includes the following steps: S1. Preparation of traditional layered double hydroxides: Dissolve soluble divalent metal ion salts and soluble trivalent metal ion salts in water to prepare metal ion salt solutions. Use double-distilled water with CO2 as a solvent to prepare urea solutions. Mix the metal ion salt solutions and urea solutions, transfer them to a hydrothermal synthesis reactor, heat at 100°C for 24 h, and dry to obtain traditional layered double hydroxides. S2. Preparation of defect-engineered LDH-based materials: Using CO2-free double-distilled water as a solvent, an alkaline solution was prepared. The traditional layered double hydroxide obtained in S1 was dispersed in the prepared alkaline solution and transferred to a hydrothermal synthesis reactor. The mixture was heated at 160°C for 5 hours and then dried to obtain the defect-engineered LDH-based material. S3. Composite magnetic iron oxide nanoparticles: The defect-engineered LDH-based material obtained in step S2 is composited with magnetic iron oxide nanoparticles to obtain a defect-engineered magnetically responsive LDH-based bone repair material.

4. The method for preparing the defect-engineered magnetically responsive LDH-based bone repair material according to claim 3, characterized in that, The concentration of the urea solution in step S1 is 0.04 M; The soluble divalent metal ion salt mentioned in step S1 is selected from either magnesium nitrate or magnesium chloride; the soluble trivalent metal ion salt is selected from either aluminum nitrate or aluminum chloride. The molar ratio of divalent metal ions to trivalent metal ions in step S1 is 3:1 to 5:1; In step S1, the ratio of the total molar amounts of urea and metal ion salt solution is 3-5:

1.

5. The method for preparing the defect-engineered, magnetically responsive LDH-based bone repair material according to claim 3, characterized in that, The alkaline solution mentioned in step S2 is a potassium hydroxide solution or sodium hydroxide solution with a concentration of 0.5-2 M; In step S2, the ratio of traditional layered double hydroxide to alkaline solution is 1.5-2 mg / mL, and the concentration of alkaline solution is 0.5-2 mol / L; In step S3, the mass ratio of the defect-engineered LDH-based material to the magnetic iron oxide nanoparticles ranges from 1:0.2 to 1:0.

8.

6. The method for preparing the defect-engineered magnetically responsive LDH-based bone repair material according to claim 3, characterized in that, In step S3, the composite magnetic iron oxide nanoparticles are adsorbed using an electrostatic adsorption method. The specific steps are as follows: (1) Disperse the prepared defect-engineered LDH-based material in double-distilled water to remove carbon dioxide and prepare an LDH-based dispersion; (2) Carboxylated iron oxide magnetic nanoparticles were dispersed in carbon dioxide-free double-distilled water to prepare a magnetic particle dispersion; (3) The carboxylated iron oxide magnetic nanoparticle dispersion was added dropwise to the LDH-based dispersion under continuous stirring. The mixture was fully mixed and reacted by electrostatic adsorption to obtain the LDH-based magnetic composite suspension. (4) The LDH-based magnetic composite suspension is washed and dried to obtain the defect-engineered magnetically responsive LDH-based bone repair material.

7. The method for preparing the defect-engineered magnetically responsive LDH-based bone repair material according to claim 3, characterized in that, In step S3, the composite magnetic iron oxide nanoparticles are synthesized using an in-situ co-precipitation method. The specific steps are as follows: (1) Dissolve soluble ferrous salts and soluble ferric salts in double-distilled water to remove carbon dioxide and prepare ferric ion precursor solutions; (2) Prepare an alkaline precipitant solution using ethylene glycol or diethylene glycol as a solvent; (3) The defect-engineered LDH-based material, iron ion precursor solution and alkaline precipitant solution prepared in step S2 are mixed and stirred until homogeneous. The mixture is then heated to 160-220 °C and reacted at a constant temperature for 4-6 h to obtain an LDH-based magnetic composite suspension. (4) The LDH-based magnetic composite suspension was washed and dried to obtain a magnetically responsive LDH-based bone repair material with defect engineering control.

8. The preparation method according to claim 7, characterized in that, The soluble ferrous salt mentioned in step (1) is selected from any one of ferrous sulfate, ferrous chloride, and ferrous nitrate; the soluble ferric salt is selected from any one of ferric sulfate, ferric chloride, and ferric nitrate. The molar ratio of ferrous ions to ferric ions in step (1) is 1:1 to 1:

2.

9. The use of the defect-engineered magnetically responsive LDH-based bone repair material according to any one of claims 1-2 in the preparation of drugs that promote osteogenic differentiation of mesenchymal stem cells and drugs for the repair and regeneration of bone defects.

10. The application according to claim 9, characterized in that, The mesenchymal stem cells mentioned are bone marrow-derived mesenchymal stem cells or osteoblastic progenitor cells.